Giant Hepatocellular Carcinoma in Cirrhotic Liver. Case Report and Literature Review - Jorge Luis Montes de Oca Mastrapa; Johnny Pérez Betancourt; Alejandro Cisneros Carmenate (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Hepatocellular carcinoma is the most common primary liver neoplasm. It is the sixth most common tumor in the world, between 500,000 and one million cases diagnosed each year, and is the second most common cause of death from cancer. The disease develops almost exclusively in patients with underlying chronic liver disease, 85 to 95 % of who have developed cirrhosis. Surgical treatment, resection or liver transplant, continues to be the choice. The case of a 55-years-old male patient with a history of health with symptoms of gastric fullness, hematemesis or melena is presented. Physical examination revealed a tumor of more than 16 centimeters palpable in the epigastrium. By abdominal ultrasonography and simple and contrasted tomography, the initial diagnosis was made of a giant hepatocellular carcinoma of more than 16 centimeters in segments II and III. Surgical resection of the tumor was performed, confirming by the anatomopathological study a well-differentiated hepatocellular carcinoma with cirrhotic liver. After 6 months of surgery, favorable clinical and tomographic evolution was confirmed. Hepatocellular carcinoma continues to be a rare entity for which surgical resection is a therapeutic option. An atypical case diagnosed and operated on for giant hepatocellular carcinoma with a cirrhotic liver is presented.